A Model of Cryptocurrencies - Sockin, Michael; Xiong, Wei (Management Science, 2023)
We model cryptocurrencies as utility tokens used by a decentralized digital platform to facilitate transactions between users of certain goods or services. The network effect governing user participation, in conjunction with the nonneutrality of the token price, can cause the token market to break down. We show that token retradeability mitigates this risk of breakdown on younger platforms by harnessing user optimism but worsens this fragility when sentiment trading by speculators crowds out users. Elastic token issuance mitigates this fragility, but strategic attacks by miners exacerbate it because users’ anticipation of future losses depresses the token’s resale value. This paper was accepted by Agostino Capponi, Special Section of Management Science: Blockchains and Crypto Economics.